Checklist of the subfamilies Mirinae and Orthotylinae (Hemiptera: Heteroptera: Miridae) in western parts of Kerman Province, Iran - Mohsen Shamsi (Arthropods, 2014)
A faunal study was carried out on the subfamilies Mirinae and Orthotylinae (Heteroptera: Miridae) from different parts of western Kerman Province on various host plants. In total 16 species belonging to 14 genera were collected and identified from different host plants and localities.